ショウワキチ ノ キコウ シリョウ - 気象庁観測部南極観測事務室; キショウチョウカンソクブナンキョクカンソクジムシツ; Office of Antarctic Observations, Observations Department, Japan Meteorological Agency (1981)
P(論文) 1957年2月に開始された昭和基地(69°00'S, 39°35'E)の地上気象観測結果のうち, 主要要素について1980年までの月および旬ごとの毎年の値とその平均値(準平年値)をまとめて示した。統計年数は要素によって異なるが, 1958年と1962～65年の基地閉鎖期間を除く14～19年間である。また, 高層気象観測については, 00Z(現地時間03時, 1968年3月開始)における指定気圧面の月別累年平均値のみを掲げた。 This report summarizes climatological data obtained at Syowa Station (index number 89532 : 69°00'S, 39°35'E, barometer elevation 21m) from 1957 to 1980 except for 5 unoccupied years. Monthly and 10-day mean and other statistical values are tabulated of sea-level air pressure, air temperature, humidity, wind speed and direction, sunshine duration, global solar radiation and cloud amount for the respective years. The results of upper-air observations are also tabulated only for the monthly mean values of height, temperature and wind speed at 8 standard levels. departmental bulletin paper